Analisis sentimen kebijakan masuk sekolah pukul lima pagi menggunakan algoritma NaÃ¯ve Bayes - Hoar, Wilhelmina Sonya; Zubair, Anis; Muflikhah, Lailil (Journal of Information System and Application Development, 2024)
Education is very important to build a quality young generation that can advance the nation. To improve the quality of education, the government of East Nusa Tenggara implemented a five am school entry policy. However, this policy has caused pros and cons in the community. People are becoming more active expressing their opinions through social media. Criticism of this policy is reflected in comments appearing on social media, especially on Twitter. Therefore, it's important to conduct sentiment analysis to know how many positive and negative responses to this policy. In this research, sentiment analysis was carried out on search results for tweets with the keyword â€œsekolah jam 5 di NTTâ€ in the time period from February to March 2023. A total of 777 tweets were obtained with 24 positive sentiments and 753 tweets with negative sentiments. The data was then processed and analyzed using the NaÃ¯ve Bayes algorithmThis research obtained accuracy results of 97% with a negative sentiment precision value of 98% and a positive sentiment precision value of 50%. In addition, the recall and f1-score values for negative sentiment are greater than positive sentiment, indicating that more people do not agree with the policy.